Sharia-Compliant MSMEs Development Strategy: Soar Approach in a Bakery Business in Tanjung Morawa - Tanjung, Rizki Ramadhan; Yafiz, Muhammad; Rahmani, Nur Ahmadi Bi (IAIN Manado, 2025)
This study aims to analyze the development of Sharia-compliant MSMEs by applying the SOAR (Strengths, Opportunities, Aspirations, Results) approach. Utilizing a qualitative case study methodology, data were collected through documentation, in-depth interviews with key stakeholders including the owner, employees, customers, and external observers, as well as direct observation to comprehensively address the research questions. The findings reveal that Roti Pakcik Tamora’s key strengths lie in consistent product quality, strong business integrity, and strict adherence to Sharia principles in all operational aspects. Strategic opportunities include the effective use of social media as a dynamic marketing tool and a rising public awareness and demand for halal products that the business can leverage. The business owner’s aspirations emphasize achieving economic success while also seeking blessings, justice, and widespread social benefits. As a result, the business has achieved measurable outcomes such as empowering the local workforce, increasing revenue, and fostering strong customer loyalty. The study concludes that the SOAR approach not only effectively integrates Sharia values into business strategies but also equips Sharia-compliant MSMEs to overcome challenges related to digitalization and market competition, fostering sustainable growth. Hence, the SOAR strategy is relevant and applicable as a replicable model for other Sharia-compliant MSMEs navigating the digital economy and halal marketing landscape.